Heme arginate potentiates latent HIV-1 reactivation while inhibiting the acute infection - Shankaran, Prakash; Vlkova, Lenka; Liskova, Jana; Melkova, Zora (Antiviral research, 2011)
Human immunodeficiency virus-1 (HIV-1) successfully escapes from host immune surveillance, vaccines and antiretroviral agents. The available antiretroviral compounds can only control viremia, but it is impossible to eliminate the virus from the organism, namely because HIV-1 provirus persists in the reservoir cells from which the virus repeatedly disseminates into new cells. Current therapeutic approaches, however, do not specifically address the stage of virus reactivation. Heme has been demonstrated as very efficient in inhibiting HIV-1 reverse transcription, while its derivative hemin ameliorated HIV-1 infection via induction of heme oxygenase-1. Normosang (heme arginate; HA) is a human hemin-containing compound used to treat acute porphyria. In this work, we studied the effects of HA in HIV-1-acutely infected T-cell lines, and in cell lines harboring either a complete HIV-1 provirus (ACH-2 cells) or an HIV-1 "mini-virus" (Jurkat clones expressing EGFP under control of HIV LTR). We demonstrate that HA inhibited HIV-1 replication during the acute infection, which was accompanied by the inhibition of reverse transcription. On the other hand, HA alone stimulated the reactivation of HIV-1 "mini-virus" and synergized with phorbol ester or TNF-α in the reactivation of HIV-1 provirus. The stimulatory effects of HA were inhibited by N-acetyl cysteine, suggesting an increased redox stress and activation of NF-κB. Further, HA induced expression of heme oxygenase-1 (HO-1) in ACH-2 cells, while HO-1 was found expressed in untreated Jurkat clones. Inhibitor of HO-1 activity, tin protoporphyrin IX, further increased HA-mediated reactivation of HIV-1 "mini-virus" in Jurkat clones, and this effect was also inhibited by N-acetyl cysteine. The stimulatory effects of HA on HIV-1 reactivation thus seem to involve HO-1 and generation of free radicals. Additionally, the effective concentrations of HA did neither affect normal T-cell activation with PMA nor induce activation of the unstimulated cells. In conclusion, HA appears to possess a combination of unique properties that could help to decrease the pool of latently infected reservoir cells, while simultaneously inhibiting HIV-1 replication in newly infected cells. Our results thus suggest a new direction to explore in treatment of HIV/AIDS disease.
Keywords: aktivace viru; hem; buněčné linie; Proviruses; Jurkat buňky; CD antigeny; Lectins, C-Type; Protoporphyrins; reverzní transkripce; metaloporfyriny; Arginine; Anti-HIV Agents; Antigens, Differentiation, T-Lymphocyte; HIV-1; lidé; replikace viru; lektiny typu C; proviry; acetylcystein; Cell Line; protoporfyriny; latence viru; hemoxygenasa-1; Humans; Antigens, CD; Heme; Metalloporphyrins; Virus Latency; arginin; diferenciační antigeny T-lymfocytů; Heme Oxygenase-1; látky proti HIV; Virus Replication; Jurkat Cells; Reverse Transcription; Virus Activation; Acetylcysteine